Strategic adoption: unveiling the impact of e-Bupot application in government agencies - Surianingsih, Kadek; Sari, Maria M Ratna; Yadnyana, I Ketut; Erawati, Ni Made Adi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
The e-Bupot application for government agencies is an information technology solution provided by the Directorate General of Taxes (DGT) of Republic of Indonesia. The e-Bupot is designed to simplify the fulfillment of tax obligations and enhance the overall convenience of taxpayers. The aim of this reseach were analysed the taxpayer’s acceptance and satisfaction levels, and also improved the understanding of taxpayer’s compliance among users of the e-Bupot application, which comprising all government agencies that registered as taxpayers in Bali Regional Office of the DGT. This research integrated the Meta-UTAUT model along with the ISS Model to analyze the acceptance of e-Bupot. Adopting a quantitative approach, the sampling technique used in this research was purposive, utilized online questionaire survey that were completed by 172 respondents. Data analysis for this research was conducted by using the PLS method with SmartPLS version 3 software. The results of this research show that some factors including the effort expectancy, information quality, service quality, system quality, attitude, trust, and behavioral intention were identified as important factors that encourage the use behavior of taxpayers in utilizing the e-Bupot application and finally influencing their tax compliance.